Tlingit grave of Dr. Skah-owa marked with totem figure, Tuxekan, Alaska, July 17, 1911. - Cobb, John N.
Grave of medicine man marked with totem figure of man holding fish. Note from Cobb field notebook: Grave of medicine man "Dr. Skah-owa" near Tuxekan, Alaska. Note from unidentified source: View of totem figure on corner, man holding fish.